Early Healing of Immediate Implants Connected With Two Types of Healing Abutments: A Prospective Cohort Study. Issue 6 (December 2018) - Hu, Chen; Lin, Weimin; Gong, Ting; Zuo, Yi; Qu, Yili; Man, Yi
Abstract : Purpose: To compare hard- and soft-tissue changes around immediate implants connected with 2 types of healing abutments during the early phases of healing. Materials and Methods: Twenty-eight immediate implants were placed into molar/premolar sockets through a modified osteotomy method. The gaps around implants were grafted with deproteinized bovine bone mineral. According to the size of the alveoli, the implants were connected with titanium healing abutments (traditional group) or customized healing abutments (CA group). Radiographic and intraoral examinations were performed before surgery, postoperatively, and at the 6-month recall. Results: Buccal ( P = 0.717) and lingual ( P = 0.087) vertical bone loss was comparable between groups. More significant incomplete defect fill was found at the distal aspect of the CA group ( P = 0.000). The buccal bone thickness alterations were similar between the 2 groups ( P = 0.902 at the implant platform). The mid-facial soft-tissue level was well maintained in both groups. Conclusions: Within the limitations of this study, for immediate implants placed into posterior sockets, customized healing abutments can facilitate closure of large sockets. Despite more pronounced incomplete defect fill, healing abutments consisting of polyether ether ketone and resin did not render an increased risk for periimplant bone loss or soft-tissue recession during the early healing period.